The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/f10100878
|View full text |Cite
|
Sign up to set email alerts
|

Social Innovation as a Prospect for the Forest Bioeconomy: Selected Examples from Europe

Abstract: Very recently, social innovation has become a subject of investigation in forest research. Earlier on, social innovation turned into a term used in EU policy strategies for addressing social issues and the self-empowerment of local people, as well as for tackling economic, social, or environmental challenges. The question of how the forest bioeconomy might profit from social innovation remains. The article examined the forest bioeconomy from the perspective of social innovation features: How is social innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
0
18
0
3
Order By: Relevance
“…Additionally, as Pol and Ville ( 2009 ) highlight, SIs have features similar to public goods; therefore, in purely private markets, there will always be an undersupply of SIs unless governments intervene. Frequent SI markets are related to social and demographic changes or the need for environmental protection (Angelidou & Psaltoglou, 2017 ; Angelini et al, 2016 ; Groot & Dankbaar, 2014 ; Ludvig et al, 2019 ; Merkel, 2020 ). Other social innovators are active in niches of mainstream markets such as food or tourism and implement social or environmental-protective aspects in their innovative approaches (Alberio & Moralli, 2021 ; Malek & Costa, 2015 ; Pellicer-Sifres et al, 2017 ).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Additionally, as Pol and Ville ( 2009 ) highlight, SIs have features similar to public goods; therefore, in purely private markets, there will always be an undersupply of SIs unless governments intervene. Frequent SI markets are related to social and demographic changes or the need for environmental protection (Angelidou & Psaltoglou, 2017 ; Angelini et al, 2016 ; Groot & Dankbaar, 2014 ; Ludvig et al, 2019 ; Merkel, 2020 ). Other social innovators are active in niches of mainstream markets such as food or tourism and implement social or environmental-protective aspects in their innovative approaches (Alberio & Moralli, 2021 ; Malek & Costa, 2015 ; Pellicer-Sifres et al, 2017 ).…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…This school is found in the southern EU and in the functional policies of low-income countries though explicit analyses of the latter are absent in the literature. Ludvig et al [44] demonstrated the relevance of non-timber forest products to foster employment and local development in Europe. In the study of the forest-based bioeconomy in Italy, Falcone et al [29] also mentioned the role of non-timber forest products in benefitting rural areas by identifying business opportunities and unlocking the associated value chains.…”
Section: Socio-bioresource Schoolmentioning
confidence: 99%
“…Pada dasarnya penurunan kelas diameter kayu HR akan mengancam kelestarian hutan dan usaha hutannya (Sanders, Ford, Keenan, & Larson, 2020). Penurunan kualitas dan kuantitas tegakan (volume, diameter, dan jumlah pohon per hektare) dapat disebabkan oleh berbagai macam faktor, di antaranya adalah penerapan silvikultur yang kurang optimal (MacDicken et al, 2015;Ludvig, Zivojinovic, & Hujala, 2019). Berbicara HR, faktor yang berpengaruh terhadap potensi tegakan menjadi lebih kompleks karena telah melibatkan faktor sosial dan ekonomi pemilik lahan HR.…”
Section: Pendahuluanunclassified